INFECTIOUS DISEASES IN CHILDREN AND THE REFLECTION ON THE VARIOUS COMMONLY USED ANTIBIOTIC AGENTS - Ali, Imran Ahmed; Muhammad Hanif; Mushtaque Ali Shah; Muhammad Sajid Noor; Tasneem Kauser; Ashique Ali Arain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Pediatric patients are the most frequent population visiting the out patent department with various illnesses round the year. Infections are among the most common reason for illness in this population. Aims: This study of cross sectional design was executed to evaluate different pediatric infections in patients visiting pediatric department of Muhammad Medical College. Methodology: A total of 506 pediatric admitted patients were assessed in pediatric department and data was collected through consecutive sampling over one-year time period and data thus obtained was evaluated in terms of frequency and percentage for various diseases and presented in tables and figures. The response towards antibiotic therapy was estimated as resolution of symptoms. Results: The male proportion of patients dominated over female proportion with 327 (64.62%) and 179 (35.38%) respectively. Most cases were of age under 1 year    286(56.52%) followed by age between 1-5 years 115(22.73%) and age group above 5years was the least affected group 105(20.75%). Gastroenteritis cases were most common followed by RTIs and non-infectious diseases. Conclusion: Gastrointestinal infections were found to be more common in pediatric patients followed by respiratory infections and the response towards Macrolides and Cephalosporin groups of antibiotics was excellent